Generation of intense phase-stable femtosecond hard X-ray pulse pairs - Zhang, Yu; Kroll, Thomas; Weninger, Clemens; Michine, Yurina; Fuller, Franklin D.; Zhu, Diling; Alonso-Mori, Roberto; Sokaras, Dimosthenis; Lutman, Alberto A.; Halavanau, Aliaksei; Pellegrini, Claudio; Benediktovitch, Andrei; et al. (Proceedings of the National Academy of Sciences - PNAS, 2022)
Coherent nonlinear spectroscopies and imaging in the X-ray domain provide direct insight into the coupled motions of electrons and nuclei with resolution on the electronic length scale and timescale. The experimental realization of such techniques will strongly benefit from access to intense, coherent pairs of femtosecond X-ray pulses. We have observed phase-stable X-ray pulse pairs containing more than 3 × 10⁷ photons at 5.9 keV (2.1 Å) with ∼1 fs duration and 2 to 5 fs separation. The highly directional pulse pairs are manifested by interference fringes in the superfluorescent and seeded stimulated manganese Kα emission induced by an X-ray free-electron laser. The fringes constitute the time-frequency X-ray analog of Young’s double-slit interference, allowing for frequency domain X-ray measurements with attosecond time resolution.